Effect of Dietary Supplementation with Sage (Salvia officinalis) and Yeast on Egg Sensory Quality and Internal Organ Characteristics of ISA Brown Laying Hens - Mohammed Hasib Mohamed (Journal of Science in Medicine and Life, 2026)
The paper analyzed how dietary supplementation with sage (Salvia officinalis) powder and yeast (Saccharomyces cerevisiae) affect the sensory properties of eggs and internal organ growth of internal organs in ISA Brown laying hens. A total of 112 hens between 60 weeks of age received eight dietary treatments comprising of a control diet, yeast supplementation and the different levels of sage powder (0.50, 1.00 and 1.50 percent) individually and in combination. Evaluations were done in egg sensory characteristics and internal organ relative weight. The findings showed no statistically significant differences (P >0.05) between the treatments of most of the egg sensory attributes implying that the addition of sage and yeast did not have a negative impact on the sensory quality of eggs. There were some slight differences in the scores of the texture but they were within acceptable range. In addition, dietary treatments failed to have a strong influence on the relative weight of the internal organs. Therefore, the use of sage (Salvia officinalis) powder alone or in conjunction with yeast (Saccharomyces cerevisiae) can be safely added to the diet of laying hens without causing any harmful effects on the sensory properties of eggs and the development of their internal organs.